Pelatihan Penulisan Karya Tulis Ilmiah bagi Mahasiswa Program Studi Pendidikan Matematika UNWAHA - Wisnu Siwi Satiti; Mucharommah Sartika Ami (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2022)
Scientific writing is a familiar academic activities to students of higher education. Since the beginning of their academic life in higher education, students have been faced with various tasks that involve scientific writing as reports. In addition, writing scientific papers is one of requirements for students in order to obtain academic degree in higher education. However, some evidenc and results of several previous studies show that students' writing skills are still low. Even though there have been supporting courses to support students in compiling scientific papers, many students consider writing scientific papers as a tough task. Therefore, it is needed for training activities to improve students' knowledge and abilities in writing scientific papers. This scientific writing training is part of service activity. The training was carried out in five meetings, they were 1) providing material on scientific writings and writing methods, 2) selecting ideas and titles of works, writing backgrounds, reviewing literature and writing references, 3) writing research methods, 4) writing results and discussions, and closing, 5) review and finalization of the works. The results of this training activity shows that students' interest in writing scientific papers is quite high. However, students' initial knowledge about scientific writing and writing methods is still low. Therefore, this scientific writing training activity is necessary. The posttest results shows that 90% of the participants experiences an increase in their writing knowledge and skills. These results indicate that this training activity is effective in helping students improve their knowledge and ability to write scientific papers.